2013
DOI: 10.1016/j.ympev.2013.01.009
|View full text |Cite
|
Sign up to set email alerts
|

A multimarker phylogeography of crested newts (Triturus cristatus superspecies) reveals cryptic species

Abstract: The crested newt Triturus cristatus superspecies is composed of five recognized species. One of these, T. karelinii sensu lato, comprises three geographically structured mitochondrial DNA lineages: 'eastern', 'central' and 'western T. karelinii'. Genetic divergence among these lineages is comparable to that of recognized crested newt species, but morphologically they are indistinguishable. Here, we conduct a multimarker phylogeographical survey to explore the evolutionary independence of these mitochondrial DN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
54
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(56 citation statements)
references
References 25 publications
0
54
0
Order By: Relevance
“…The first hint of T. ivanbureschi representing a distinct species came from deep genetic divergence of mitochondrial DNA (Wielstra & Arntzen, 2011;Wielstra et al, 2010). These lineages were subsequently found to differ in environmental space and were eventually confirmed to also represent discrete nuclear gene pools (Wielstra et al, 2013a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first hint of T. ivanbureschi representing a distinct species came from deep genetic divergence of mitochondrial DNA (Wielstra & Arntzen, 2011;Wielstra et al, 2010). These lineages were subsequently found to differ in environmental space and were eventually confirmed to also represent discrete nuclear gene pools (Wielstra et al, 2013a).…”
Section: Introductionmentioning
confidence: 99%
“…Wielstra et al (2013c) failed to obtain genetic data for the type material of T. arntzeni, presumably because of DNA degradation. Nuclear data available for other individuals from Vrtovać concerned just three markers, which was insufficient for a detailed examination of the newts' genetic composition (Wielstra et al, 2013a). The distribution of Triturus newts in eastern Serbia is intricate, but so much is clear that four species -next to T. ivanbureschi and T. macedonicus also T. cristatus (Laurenti, 1768) and T. dobrogicus (Kiritzescu, 1903) -are in parapatry (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Based on a detailed phylogeographical survey of three nuclear DNA markers, the presence of three genetically distinct nuclear gene pools within T. karelinii s. l. was confirmed (Wielstra et al, 2013a), that we refer to as an eastern, a central and a western T. karelinii s. l. nuclear gene pool. The distribution of these nuclear gene pools corresponds to the three mitochondrial DNA lineages, with the exception of northwestern Asiatic Turkey, where western T. karelinii s. l. mitochondrial DNA is observed in the central T. karelinii s. l. nuclear gene pool (Fig.…”
Section: Introductionmentioning
confidence: 67%
“…1). Wielstra et al (2013a) suggested that partial geographical replacement of the western nuclear gene pool by the central T. karelinii s. l. nuclear gene pool coincided with asymmetric introgression of mitochondrial DNA. For a full biogeographical scenario of T. karelinii s. l., see Wielstra et al (2013a); .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation